2000
DOI: 10.1046/j.1365-313x.2000.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of a novel diacylglycerol kinase in tomato leads to a calmodulin‐binding isoform

Abstract: Summary Calmodulin is a regulatory protein activated during Ca2+ signalling. We have isolated a cDNA, designated LeCBDGK (Lycopersicon esculentum calmodulin‐binding diacylglycerol kinase) encoding a novel calmodulin‐binding protein with sequence similarity to diacylglycerol kinases from animals. Diacylglycerol kinases convert diacylglycerol to phosphatidic acid. We delineated the calmodulin‐binding domain to approximately 25 residues near the C‐terminus of LeCBDGK. We have also isolated a second diacylglycerol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 56 publications
2
52
0
1
Order By: Relevance
“…Furthermore, biochemical studies are required to demonstrate that the predicted proteins indeed code for enzymatically active DGKs, namely in the absence of a DAG/PE-binding domain. However, as mentioned before, earlier studies have shown that tomato LeDGK1, which lacks such a domain, exhibits diacylglycerol kinase activity upon heterologous expression in E. coli (17).…”
Section: Atdgk2 and Related Plant Dgk Isozymes Contain A Unique Aggrementioning
confidence: 81%
See 2 more Smart Citations
“…Furthermore, biochemical studies are required to demonstrate that the predicted proteins indeed code for enzymatically active DGKs, namely in the absence of a DAG/PE-binding domain. However, as mentioned before, earlier studies have shown that tomato LeDGK1, which lacks such a domain, exhibits diacylglycerol kinase activity upon heterologous expression in E. coli (17).…”
Section: Atdgk2 and Related Plant Dgk Isozymes Contain A Unique Aggrementioning
confidence: 81%
“…Generation of the AtDGK5␤ splice variant is also evident from serial analysis of gene expression (SAGE) experiments, deposited in the NCBI GEO expression data repository (GEO Data Set accession number GDS101). Importantly, splice variants have also been reported for LeDGK1 from tomatoes (17). Whereas LeDGK1 itself does not bind calmodulin, the LeCB-DGK protein, which is encoded by an alternatively spliced transcript, contains a calmodulin-binding domain at its very C terminus.…”
Section: Atdgk2 and Related Plant Dgk Isozymes Contain A Unique Aggrementioning
confidence: 98%
See 1 more Smart Citation
“…Samples were either assayed immediately for NADK activity or were frozen in liquid nitrogen and stored at 280°C. Recombinant NADK2, which is able to bind CaM-agarose, was purified using CaM-affinity chromatography essentially as described (Snedden and Blumwald, 2000). The soluble bacterial extract containing recombinant NADK2 was adjusted to a final concentration of 3.0 mM CaCl 2 and loaded onto a CaM-agarose affinity column (300 mL) preequilibrated with CaM-binding buffer (50 mM Tris-HCl, pH 7.5, 1 mM CaCl 2 , 10% [w/v] glycerol, 1 mM DTT, and 1 mM PMSF).…”
Section: Expression and Purification Of Recombinant Nadksmentioning
confidence: 99%
“…CaM81-AF532 interacting proteins were detected by fluorescence imaging using a Typhoon 8600 phosphor imager (Uppsala) at excitation and emission wavelengths of 532 and 555 nm, respectively. A GST-fusion protein containing the CaM-binding domain of tomato diacylglyerol kinase (Snedden and Blumwald, 2000) was used as a positive control for CaM81-AF532 binding.…”
Section: Fluorescent Labeling Of Cam81 and Use In Overlay Assaysmentioning
confidence: 99%